(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aims to measure the effectiveness of media content in crisis communication management among official spokespersons in government entities in Saudi Arabia. It is situated within the rapid transformations of institutional communication and the growing reliance on digital media and social networking platforms for information dissemination and public engagement. The study is grounded in a central research problem concerning the need to analyze the nature of media messages delivered by official spokespersons during crises, and the extent to which such messages achieve clarity, credibility, and timely response, thereby enhancing public trust and limiting rumors and inaccurate information. The study adopts a mixed-method approach that combines quantitative and qualitative methods. A questionnaire is used to measure the perceptions of official spokespersons in Saudi government entities regarding the characteristics, formulation, and effectiveness of media content during crises. In addition, content analysis is employed to examine actual media messages issued in crisis situations, including press releases, digital posts, and official videos. The study is theoretically grounded in Media Richness Theory, which provides an appropriate framework for understanding how media diversity, interactivity, and message richness contribute to improving communication quality during crises. The significance of this study lies in its focus on the official spokesperson as a central actor in government crisis communication and as a formal media interface responsible for delivering accurate, transparent, and credible messages. The study seeks to provide an analytical framework that may assist government entities in developing more effective media content, improving institutional communication strategies during emergencies, and strengthening their ability to manage public trust and protect institutional reputation in a media environment characterized by speed, interactivity, and multiple information sources.